Sidewalk and Pedestrian Crossing Design on Urban Mixed Land Use Area - Louise Elizabeth Radjawane; Hanna Mariani Singgih; Sarliati Allo Rampa (Andalasian International Journal of Applied Science, Engineering and Technology, 2026)
Pedestrian pathways are physical infrastructure that support the smooth movement of people from one place to another. The sidewalk on Sultan Alauddin Street in Kota Makassar is damaged and has been repurposed as a parking space for motorcycles and street vendors. Pedestrians in this area are forced to use the road shoulder to walk, despite the significant safety risks for pedestrians and other road users. The purpose of this study is to determine the characteristics of pedestrians, sidewalk and pedestrian crossing planning. The references used as guidelines are Pedestrian Facility Planning, 2017. Research methods for sidewalks and pedestrian crossings generally involve several stages to measure and analyze the geometric conditions of sidewalks, pedestrian behavior, and the volume of pedestrian movement crossing the road. The sidewalk width meeting the needs of pedestrians in this section is 1.698 meters, and a pelican crossing with a duration of 94 seconds for crossing the road. Findings of the research is the average speed of pedestrian space has a positive effect on the space, but a negative effect on density. As the average speed of pedestrian space increases, the density will decrease and the space will increase.